Decentralization and Party Politics in the Dominican Republic - Mitchell, C. author. aut Link
XII, 137 p.
Keywords: Recently in the Dominican Republic, a pro-municipal social alliance pressed for decentralization and politicians yielded, seeking power in three-party competition. This study examines how electoral, financial, and administrative power has been dispersed and suggests innovative strategies to maintain decentralizing momentum.